SISTEM INFORMASI REKAM MEDIS PASIEN RAWAT JALAN DI UPTD PUSKESMAS KUNINGAN BERBASIS WEB - Tatang Saputra; Erik Kurniadi (NUANSA INFORMATIKA, 2019)
Puskesmas is a level 1 health facility. More than 40% of Indonesia's population uses health services at the Puskesmas. It is interesting that the Puskesmas is the health care provider that is closest to the community. Recording medical records of patients at the Kuningan Health Center is still done manually. Data search has time constraints. This happens because the same data is often found. Ineffective management of medical records will become a major problem in health services at the Puskesmas. This problem must be overcome so that the puskesmas has good data and information. One way to overcome this problem is to build a computerized medical record information system. Medical Record is a compilation of facts about the health and illness of a patient. Medical Records become a very important thing in the delivery of health services. Because the importance of a medical record, the author is interested in conducting research with the title "Information Systems for Outpatient Medical Records in UPTD Puskesmas Kuningan Web-Based". The medical record information system is expected to help improve the function of the Puskesmas as a place of health care. With the existence of a medical record system, each patient visit can be taken in a database making it easier for officers in the process of finding medical record data when needed. With the database, the compilation of patients forgetting to bring a treatment card can be done by searching the patient's data by the electronic officer. Making a report will be easier because it retrieves data that is done through the request system so as to facilitate the process and minimize errors in data management.Keywords: php, mysql, medical record, outpatient